RELATIONSHIP OF ABSTINENCE BEHAVIOR, BEING FAITHFUL, CONDOM USE, AND DRUG USE TO THE INCIDENCE OF SEXUALLY TRANSMITTED INFECTIONS IN MARRIED MEN SEX MEN IN INDONESIA - Purba, Rispah; Chatleen Compehage Mollet, Genoveva; Bella, Sarni Rante Allo; Fatiah, Mona Safitri (JURNAL KESEHATAN REPRODUKSI, 2024)
Background: The monogamous sexual behavior of married men who have sex with men (MSM) increases their risk of acquiring sexually transmitted infections (STIs). This study aims to examine the influence of ABCD behaviors on the incidence of STIs among married MSM in Indonesia. Method: A cross-sectional study was conducted in 24 provinces in Indonesia. The study population comprised MSM who had ever engaged in sexual intercourse, either occasionally, once, or frequently, totaling 6,000 individuals. A sample of 775 participants who were married MSM was selected using the Respondent Driven Sampling (RDS) method. Data from the Integrated Biological and Behavioral Survey (STBP) 2018-2019 was utilized. The data was analyzed using multivariate analysis with STATA 14 software. Results: The variables of no vaginal sex, no anal sex, condom use, and needle drug use behavior are associated with the incidence of STIs when controlled by the variable of alcohol consumption behavior. Conclusion: Practicing ABCD behaviors among married MSM can help reduce and prevent STIs.